Development planning at upazila level - Ali, M. Hazrat (Comilla : Bangladesh Academy for Rural Development, 1987)
With special reference to Mymensingh District, Bangladesh.
Master microform held by: DLC.
Bibliography: p. 90.
Keywords: Rural development -- Bangladesh